Emperors and Political Culture in Cassius Dio's Roman History - Davenport, Caillan; Mallan, Christopher (Cambridge : Cambridge University Press, 2021)
The Roman History of Cassius Dio provides one of the most important continuous narratives of the early Roman empire, spanning the inception of the Principate under Augustus to the turbulent years of the Severan Dynasty. It has been a major influence on how scholars have thought about Roman imperial history, from the Byzantine period down to the present day, as well as being a work of considerable literary sophistication and merit. This book, the product of an international collaborative project, brings together thirteen chapters written by scholars based in Europe, North America, and Australia. They offer new approaches to Dio's representation of Roman emperors, their courtiers, and key political constituencies such as the army and the people, as well as the literary techniques he uses to illuminate his narrative, from speeches to wonder narratives.
Introduction: Cassius Dio: The Senator and his Caesars -- I, Imperial and political narratives -- 1, Vox populi, vox mea? Information, evaluation and public opinion in Dio's account of the principate -- 2, News, rumour, and the political culture of the roman imperial monarchy in the Roman History -- 3, Literary and documentary sources in Dio's narrative of the roman emperors -- 4, "Now comes the greatest marvel of all!" (79(78).8.2): Dio's roman emperors and the incredible -- II, Emperors and biographies -- 5, Cassius Dio's funeral speech for Augustus: sources, rhetoric, messages -- 6, "... But he possessed a most singular nature": Cassius Dio on Tiberius -- 7, An Emperor's war on Greece: Cassius Dio's Nero -- 8, War and peace: imperial leadership in Dio's second-century narrative -- III, Political groups and political culture -- 9, "The people" and Cassius Dio -- 10, Citizenship, enfranchisement and honour in Cassius Dio -- 11, The company they keep: Emperors and their associates -- 12, Dio and his friends: Autobiography and biography in Cassius Dio's contemporary narrative -- IV, Reception and reflection -- 13, The reception of Cassius Dio's imperial narrative in Byzantium (tenth-twelth centuries) -- Epilogue: And now...?
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Dio Cassius, -- asi 155-235.; 2.-3. století; 1. století př. Kr.-3. století po Kr; historiografie -- starověký Řím -- 2.-3. století; panovníci -- starověký Řím -- 1. století př. Kr.-3. století po Kr; historiography -- ancient Rome -- 2nd-3rd centuries; kings and rulers -- ancient Rome -- 1st century B.C.-3rd century A.D.; starověký Řím -- politika a vláda -- 1. století př. Kr.-3. století po Kr; starověký Řím -- historiografie; ancient Rome -- politics and government -- 1st century B.C.-3rd century A.D.; ancient Rome -- historiography; e-knihy online; sborníky konferencí; proceedings of conferences; e-books online